Policy support for disruptive innovation in the life sciences. Issue 3 (4th March 2021) - Tait, Joyce; Wield, David
ABSTRACT: This paper focuses on business models and value chains to analyse sectoral innovation systems involving synthetic biology and gene editing, as potentially disruptive platform technologies in the life sciences. In the context of industrial biotechnology, we propose that the extent to which an innovation is expected to be disruptive, and the location of that disruption in existing value chains, are relevant to policy decision making on how to govern innovative technologies. Policy decisions on how to regulate or support an innovative technology will be among the most important factors determining the extent to which it is able to deliver its disruptive potential, leading to sectoral transformations through new business models and value chains. This mode of thinking about disruption and innovation could be incorporated in standard procedures for policy makers to guide decisions designed to support translation from basic scientific research to societally useful products and processes.